A Pandemic Business Interruption Insurance - Alexis Louaas; Pierre Picard (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We analyze how pandemic business interruption coverage can be put in place by building on capitalization mechanisms. The pandemic risk cannot be mutualized since it affects simultaneously a large number of businesses, and furthermore, it has a systemic nature because it goes along with a severe decline in the real economy. However, as shown by COVID-19, pandemics affect economic sectors in a differentiated way: some of them are very severely affected because their activity is strongly impacted by travel bans and constraints on work organisation, while others are more resistant. This opens the door to risk coverage mechanisms based on a portfolio of financial securities, including long-short positions and options in stock markets. We show that such financial investment allow insurers to offer business interruption coverage in pandemic states, while simultaneously hedging the risks associated with the alternation of bullish and bearish non-pandemic states. These conclusions are derived from a theoretical model of corporate risk management, and they are illustrated by numerical simulations, using data from the French stock exchange.
Keywords: G11; G22; G32; 330; pandemic; business interruption; insurance; corporate risk management